The Impacts of Time Pressure and Emotion on the Information Behavior of High Stakes Decision Makers: The Home Buying Experience - Landry, Carol Fay (My University, 2015)
Decisions. As we move through our everyday activities, we make decisions. Many are routine, do not involve risk or focus on a single issue. We know what to expect. Some decisions, however, entail risk and uncertain outcomes. Such decisions are referred to as "high stakes" This dissertation determined how time pressure and emotion influence people's information behavior when engaging in high stakes decision-making within the home buying domain. Additionally, the study tested Chatman's Theory of Normative Behavior (Chatman, 2000) and ascertained the helpfulness of deciders' Information Grounds (Fisher, Durrance, & Hinton, 2004). By examining these phenomena, I expand the information behavior knowledge base. Employing an exploratory approach, I performed a deep, reflective ersatz home buying experience, conducted 33 semi-structured interviews using a timeline strategy and carried out eight observations with participants from the Seattle, Washington metropolitan area. Participants included homebuyers and home buying stakeholders such as real estate agents, lenders and escrow agents. Data were collected from April 2012 through March 2013. Findings revealed that "information use" induce emotion and a sense of time pressure, whereas all other "non-information use" behaviors are propelled by emotion and time pressure. The study also identified the emergent theme "information use by proxy" phenomenon wherein emotions prompt people to forgo information responsibility and enlist trusted surrogates to use information on their behalf. Further, findings show that emotion and time pressure have the ability to alter one's routine information behavior, which can result in shared dyadic information behavior between couples. Moreover, the behavior has implications for such relationships as found in the business world, academia, artistic endeavors and other collaborations (Papadopoulou, Lee, Fisher, 2013). From theory testing, the study found that Chatman's Theory of Normative Behavior explains high stakes deciders' information behavior, but demonstrates limitations regarding the "information behavior" aspect of the theory. As a result, I propose a new, holistic information behavior definition to buttress Chatman's theoretical framework. The study also ascertained that Fisher's Information Grounds provide helpful information for most, but not all high stakes decision makers since sharing information with strangers went against one's nature, information was not relevant or trustworthy or people had insufficient time to socialize. Social information used for light conversation, however, was considered valuable to home buying stakeholders as such information helps to build and maintain relationships, which is viewed as a vital component of successful businesses in the competitive field of residential real estate. Lastly, study findings demonstrate relevance to other fields like medicine, emergency and disaster management or social and political science as issues of emotion and time pressure are likely to present in myriad and unanticipated ways.
Thesis (Ph.D.)--University of Washington, 2014
Keywords: decision-making; emotion; Information behavior; Information Grounds; Theory of Normative Behavior; time pressure; Information science; information science